Determinant factors of adoption of Fintech Payment Services in Indonesia using the UTAUT approach / Florentina Kurniasari ... [et al.] - Kurniasari, Florentina; Tajul Urus, Sharina; Utomo, Prio; Abd Hamid, Nadiah; Jimmy, So Yohannes; Othman, Intan Waheedah (Accounting Research Institute (ARI), 2022)
The advancement of digital technology has affected many industries, including digital payment services. The objective of this study was to analyze the adoption of Fintech payment services in Indonesia using the UTAUT theory approach. This study also considered the important role of national culture in strengthening the effect of the social influence variable in creating trust. The study added the government policy variable in strengthening the effect of facilitating a condition in creating trust. The study was conducted by distributing 310 questionnaires to freshly employed graduates who were digital payment services users. Further analysis was conducted with linear multiple regression using IBM SPSS 26. The study found that trust had the highest effect in creating the adoption decision in digital payment services, followed by government policies in strengthening the facilitating conditions. Meanwhile, performance and effort expectancy, social influence and facilitating condition did not have a direct influence on customer trust. Uncertainty avoidance, masculinity and long-term orientation also did not have a strengthening effect of social influence in gaining trust.